Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Murphy, Angela M.; MacHugh, David E.; Park, Stephen D.E.; Scraggs, Erik; Haley, Chris S.; Lynn, David J.; Boland, Maurice P.; Doherty, Michael L. (Mammalian genome, 2007)
Arthrogryposis is a congenital malformation affecting the limbs of newborn animals and infants. Previous work has demonstrated that inherited ovine arthrogryposis (IOA) has an autosomal recessive mode of inheritance. Two affected homozygous recessive (art/art) Suffolk rams were used as founders for a backcross pedigree of half-sib families segregating the IOA trait. A genome scan was performed using 187 microsatellite genetic markers and all backcross animals were phenotyped at birth for the presence and severity of arthrogryposis. Pairwise LOD scores of 1.86, 1.35, and 1.32 were detected for three microsatellites, BM741, JAZ, and RM006, that are located on sheep Chr 5 (OAR5). Additional markers in the region were identified from the genetic linkage map of BTA7 and by in silico analyses of the draft bovine genome sequence, three of which were informative. Interval mapping of all autosomes produced an F value of 21.97 (p < 0.01) for a causative locus in the region of OAR5 previously flagged by pairwise linkage analysis. Inspection of the orthologous region of HSA5 highlighted a previously fine-mapped locus for human arthrogryposis multiplex congenita neurogenic type (AMCN). A survey of the HSA5 genome sequence identified plausible candidate genes for both IOA and human AMCN.